Integration of Artificial Intelligence in Clinical Laboratory and Pharmacy Services: A Systematic Review of Applications in Saudi Healthcare - Mujbel Fahad M Aldhafeeri, Mseerah Jabar F Aldhafeeri, Fayez Khalaf Mashan Alanazi, Munirah Mathhur Fawaz Aldahmashi, Alanoud Saleh Hamoud Aldhafeeri, Hamoud Zaal Saud Alshammari (Journal of International Crisis and Risk Communication Research, 2024)
The integration of artificial intelligence (AI) in healthcare has gained significant attention in recent years, particularly in the domains of clinical laboratory and pharmacy services. This systematic review aims to synthesize the current literature on AI applications in clinical laboratory and pharmacy services within the context of Saudi healthcare. A comprehensive search was conducted in PubMed, Scopus, and Web of Science databases for studies published between 2010 and 2023. The search terms included "artificial intelligence," "clinical laboratory," "pharmacy," and "Saudi Arabia." The methodological quality of the included studies was assessed using the Mixed Methods Appraisal Tool (MMAT). A total of 18 studies met the inclusion criteria, comprising 10 quantitative, 5 qualitative, and 3 mixed-methods studies. The findings suggest that AI applications in clinical laboratory services focus on enhancing diagnostic accuracy, optimizing workflow, and improving efficiency. In pharmacy services, AI is primarily used for medication management, drug discovery, and patient counseling. However, several challenges to the widespread adoption of AI in Saudi healthcare were identified, such as lack of technical expertise, data privacy concerns, and resistance to change. The review highlights the need for further research to evaluate the long-term impact of AI on patient outcomes, healthcare costs, and professional roles in the Saudi healthcare system.